Hippocampal [(18)F]flortaucipir BP(ND) corrected for possible spill-in of the choroid plexus retains strong clinico-pathological relationships - Wolters, Emma E (Neuroimage Clin, 2019)
BACKGROUND: Off-target [(18)F]flortaucipir (tau) PET binding in the choroid plexus causes spill-in into the nearby hippocampus, which may influence the correlation between [(18)F]flortaucipir binding and measures of cognition. Previously, we showed that partial volume correction (combination of Van Cittert iterative deconvolution and HYPR denoising; PVC HDH) and manually eroding the hippocampus resulted in a significant decrease of the choroid plexus spill-in. In this study, we compared three different approaches for the quantification of hippocampal [(18)F]flortaucipir signal using a semi-automated technique, and assessed correlations with cognitive performance across methods. METHODS: Dynamic 130 min [(18)F]flortaucipir PET scans were performed in 109 subjects (45 cognitively normal subjects (CN) and 64 mild cognitive impairment/Alzheimer's disease (AD) dementia patients. We extracted hippocampal binding potential (BP(ND)) using receptor parametric mapping with cerebellar grey matter as reference region. PVC HDH was performed. Based on our previous study in which we manually eroded 40% ± 10% of voxels of the hippocampus, three hippocampal volumes-of-interest (VOIs) were generated: a non-optimized 100% hippocampal VOI [100%], and combining HDH with eroding a percentage of the highest hippocampus BP(ND) voxels (i.e. lowering spill-in) resulting in optimized 50%[50%HDH] and 40%[40%HDH] hippocampal VOIs. Cognitive performance was assessed with the Mini-Mental State Examination (MMSE) and Rey auditory verbal learning delayed recall. We performed receiver operating characteristic analyses to investigate which method could best discriminate MCI/AD from controls. Subsequently, we performed linear regressions to investigate associations between the hippocampal [(18)F]flortaucipir BP(ND) VOIs and MMSE/delayed recall adjusted for age, sex and education. RESULTS: We found higher hippocampal [(18)F]flortaucipir BP(ND) in MCI/AD patients (BP(ND100%)=0.27±0.15) compared to CN (BP(ND100%)= 0.07±0.13) and all methods showed comparable discriminative effects (AUC(100%)=0.85[CI=0.78–0.93]; AUC(50%HDH)=0.84[CI=0.74–0.92]; AUC(40%HDH)=0.83[CI=0.74–0.92]). Across groups, higher [(18)F]flortaucipir BP(ND) was related to lower scores on MMSE (standardized β(100%)=-0.38[CI=-0.57−0.20]; β(50%HDH)= -0.37[CI=-0.54−0.19]; β(40%HDH)=-0.35[CI=-0.53−0.17], all p<0.001) and delayed recall (standardized β(100%)=-0.64[CI=-0.79−0.49]; β(50%HDH)= -0.61[CI=-0.76−0.46]; β(40%HDH)=-0.59[CI=-0.75−0.44]; all p<0.001), with comparable effect sizes for all hippocampal VOIs. CONCLUSIONS: Hippocampal tau load measured with [(18)F]flortaucipir PET is strongly associated with cognitive function. Both discrimination between diagnostic groups and associations between hippocampal [(18)F]flortaucipir BP(ND) and memory were comparable for all methods. The non-optimized 100% hippocampal VOI may be sufficient for clinical interpretation. However, proper correction for choroid plexus spillover and may be required in case of smaller effect sizes between subject groups or for longitudinal studies.